A Experiência de Enfrentamento a um Contexto de Pandemia por um Grupo de PIBID: Tecnologias Digitais e Educação Matemática - Juliana Leal Salmasio (2024)
This thesis, written in a multipaper format, was developed within the Digital Technologies, Mobility, and Mathematics Education Research Group (TeDiMEM) of the Graduate Program in Mathematics Education (PPGEduMat/UFMS) and is part of the Digital Humanized Mathematics Project (MaDHu). The research problem addressed was: “How did Digital Technologies participate in the development of a PIBID mathematics group during the pandemic?” Thus, the main objective was to analyze the roles of Digital Technologies in a Mathematics PIBID group at UFMS within the context of emergency remote teaching. The discussion was based on three pillars: PIBID as a space for initial teacher training, the COVID-19 pandemic, and the use of Digital Technologies during the Emergency Remote Teaching (ERT) process. This qualitative research involved a group of eight mathematics teacher education students from the Federal University of Mato Grosso do Sul (UFMS) who participated in PIBID between 2020 and 2022, during the program's 18-month duration. Data collected during this period included recordings of 32 PIBID meetings, meeting minutes, videos produced by PIBID participants to meet school demands, three interviews with PIBID participants, portfolios documenting their trajectories, digital narratives marking the conclusion of activities, and an interview with the mathematics area coordinator of PIBID who led the group during the COVID-19 pandemic. These data were analyzed in three chapters. The findings highlight that PIBID activities were made possible, though not exclusively, through the available technologies. It was also evident that Digital Technologies underwent significant transformation during this period. The study concludes that Digital Technologies had a substantial impact on PIBID/INMA, acting as collaborative agents with the participants, especially during Emergency Remote Teaching. Despite challenges such as limited access to devices and internet, the program adapted by creating accessible materials integrated with printed resources sent by the school to mitigate inequalities. The observed "ubiquitous agency" underscores the collaboration between people and technologies, supporting education in a challenging context marked by the pandemic and structural limitations.